(untitled) (Research, Society and Development, 2020)
Brazilian fruit culture has great importance in the economy, appearing as the third largest world producer. In this context, weed management becomes indispensable from an agronomic point of view, as they compete for water, light, nutrient and space, causing many losses to the crops of interest. These losses are accentuated as they are not properly controlled, for this reason, a phytosociological survey is carried out, which allows us to know the dynamics of weeds and their correct identification. The objective of this work was to carry out a phytosociological survey of weeds existing in the cultivation of temperate fruit in the municipality of Lavras-MG. The survey was carried out in the Fruit Sector of the Federal University of Lavras (UFLA). A phytosociological survey was carried out on 18 cultivars of Pereira (Pyrus spp.), Seven cultivars of Macieira (Malus domestica L.), 22 cultivars of Pessegueiro (Prunus persica (L.) Batsch), seven cultivars of Raspberry, ten cultivars of Blackberry -Black (Rubus spp.), In addition to an area planted with 11 cultivars of Caquizeiro (Diospyrus kaki L.), a cultivar of Figueira (Ficus carica L.) and 34 cultivars of Quince (Cydonia oblonga and Chaenomelis sinensis L.). The identifications of the weeds were based on material analysis, photographs and consulting the specialized literature, afterwards the identification, there was the classification and analysis of the community structure, grouping it into families, scientific name, common name and as to the cycle plant productive species. Spatial Distribution, Variance, Density, Frequency, Constancy, Dominance, Importance Value, Importance Value Index and Similarity Assessment were evaluated. The phytosociological survey showed that the species Cyperus rotundus was the species with the highest IVI in the cultivation of mulberry, raspberry, apple and quince. While the Cynodon dactylon species had the highest IVI in the cultivation of raspberries, pear and quince. On the other hand, the Brachiaria plantaginea species reached the highest IVI in the cultivation of apple trees. Finally, the Pennisetum clandestinum species reached the highest IVI in persimmon cultivation.